Burkitt Lymphoma Presenting as Perforated Appendicitis. Issue 3 (March 2022) - Shaw, Taylor; Cockrell, Hannah; Panchal, Ramola; Abraham, Anu; Sawaya, David
Appendicitis is the most common indication for an emergent abdominal operation in the pediatric population. Fewer than .015% of patients who undergo appendectomy for presumed appendicitis are diagnosed with primary lymphoma after evaluation of pathology specimen. 1 Of these primary lymphomas, 29.5% are Burkitt lymphoma. Burkitt lymphoma is an aggressive B-cell lymphoma characterized by translocation and dysregulation of the c-Myc gene. Intraabdominal extranodal Burkitt lymphoma has a polymorphic presentation that includes bowel obstruction, intussusception, and appendicitis. Here we report a case of an adolescent patient who was initially admitted for medical management of perforated appendicitis but was diagnosed with Burkitt lymphoma during his hospital course.